RAZEM CZY OSOBNO, CZYLI O POTRZEBIE ZINTEGROWANEJ OCHRONY DZIEDZICTWA KULTUROWEGO I PRZYRODNICZEGO W DZIAŁALNOŚCI URZĘDÓW KONSERWATORSKICH - Jakub Lewicki (Ochrona Dziedzictwa Kulturowego, 2016)
Before 1945, protection of monuments and sites and nature conservation had been a single field. After this year, however, they were separated and hence, both fields are nowadays independent of each other and develop in different directions. It has been emphasised for a number of years that cooperation and symbiosis between protection of monuments and sites and nature conservation need to be improved. It has been even suggested that both fields, for which different offices and two ministries are responsible, should be joined. This aim needs to be achieved not only due to the ways in which these fields function but also in order to increase their importance. New legal acts which emphasise the significance of cultural and natural heritage in managing and shaping the surrounding areas have come into force. Moreover, descisions pertaining to protection of cultural and natural heritage became more important and the changes to the body of law and ownership rights resulted in these decisions being risen to higher rank. As cultural and natural heritage protection intertwine each other, it is necessary to introduce integrated protection in both fields. This necessity is emphasised not only in a considerable number of legal acts and international documents but also in practical solutions applied in offices whose members of staff are responsible for nature conservation and protection of historic monuments and sites. Integrated protection can be also a successful attempt at strengthening the increasingly ineffective monument protection system. Increased cooperation between these two fields as well as their connection can be a strong impetus to develop practical aspects in protection of cultural and natural heritage. It can additionally result in creating new tools which government bodies would be able to use for protecting historic monuments and sites – it must be emphasised that this protection, in order to be effective and successful, needs to be adapted to the changing reality and needs to be ready to face challenges posed by the modern world.